Potensi Anthelmintik Ekstrak Etanol Daun Mangga Arumanis (Mangifera indica L.) pada Cacing Ascaridia galli dan Raillietina tetragona secara In Vitro - Robiyanto, Robiyanto; Kusuma, Ria; Untari, Eka Kartika (UI Scholars Hub, 2018)
Arumanis mango (Mangifera indica L.), a medicinal plant, is allegedly potential as an anthelmintic agent. This research aimed to investigate the in vitro anthelmintic activity of ethanolic extract of arumanis mango leaves against Ascaridia galli and Raillietina tetragona; know the effect of increasing extract concentration; and calculate the LC50 and LT50 value of the extract. The extract concentrations tested were 5, 25 and 50 (mg/ml) with normal control (NaCl 0,9%) and positive control (mebendazole 5 mg/ml). The time and number of worm deaths were observed and analyzed statistically using One Way Anova SPSS, Post hoc (LSD) and Probit. The results showed that ethanolic extract had anthelmintic activity in which concentration of extract at 25 mg/ml and 50 mg/ml had death time and number of death worms similar to mebendazole 5 mg/ml for A. galli (p=0.466 and p=0.760) and R. tetragona (p=0.093 and p=0.566); the increasing of extract concentration was linear with the increase of its anthelmintic activity; and LC50 dan LT50 value of the extract for A. galli were 2,6 mg/ml and 15,2 hours, while for R. tetragona were 3,1 mg/ml and 2,5 hours. As a conclusion, arumanis mango leaves is potential to be developed as an anthelmintic traditional medicine.